Field notes contributed by Stephen J. Dinsmore, fall 1996 - Dinsmore, Stephen J.et al (1996)
List of birds and locations contributed by Stephen J. Dinsmore with observers Robert I. Cecil, Raymond L. Cummins, James J. Dinsmore, Francis L. Moore and others. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1996. Epson - sheet feed